Seeing God in Sufi Qur'an commentaries : crossings between this world and the otherworld - Coppens, Pieter (Edinburgh Studies in Islamic Apocalypticism and Eschatology Ser., 2018)
The first in-depth study of the concept of the vision of God in Sufi eschatology, not only focusing on the hereafter, but also on this-worldly vision.